Tele-Health Intervention for Carers of Dementia Patients—A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhu, Aiyong; Cao, Wenting; Zhou, Yinghua; Xie, Anan; Cheng, Yun; Chu, Shu-Fen (Frontiers in Aging Neuroscience, 2021)
Objective: The purpose of this study is to evaluate the major mental health outcomes on the carers of dementia patients through the psychoeducational programs and psychotherapeutic interventions. Methods: A meta-analysis was performed with randomized controlled trials of carers’ tele-health interventions updating the literature inception to December 31, 2019, from database PubMed, EMBASE, and CENTRAL for articles. Results: The meta-analysis identified 1,043 results, of which 11 were randomized control trials. Among all 11 randomized control trials, only one study addressed the face-to-face contacts with online modules of interventions, 4 studies addressed telephone-based interventions, 2 studies reported combines face-to-face contacts and phone calls of interventions, 2 studies focused on web-based intervention, one study using video and telephone interventions, and one study conducted computer-telephone integration system of intervention. The updated evidence suggested that there was more efficacy via tele-health interventions lowering depression for carers of people with dementia. We outlined the delivery formation of intervention to evaluate the effectiveness and process of major mental health improvements, including depression, burden, anxiety, and quality of life. Conclusions: In this study, tele-health intervention was significantly lowering depression and also lower the risk mental health impairment. Although there was a significant decrease of depression, there were no significant differences in burden, anxiety, and quality of life. Future researchers are encouraged to take larger-scale studies, also further analysis using a standardized assessment tool is suggested for future multi-component tele-health interventions.